Qualidade de vida e meio ambiente:: experiência de consolidação de indicadores de sustentabilidade em espaço urbano (Sustainability in Debate, 2013)
The use of indicators for diagnosing the reality of urban spaces has been a trend, given that inequitiesare materialized in the distribution of social, economic or environmental resources. This studyaimed at developing a system of environmental quality and urban life indicators, our empiricalfocus is on the urban area of Formosa in the State of Goias in Brazil. From the analysis of the factorsthat underlie experiences in building social and environmental indicators, we sought to identifyurban elements that portray the environmental, social, economic, cultural and political sustainabilitywith the participation of local social actors. The development of a system of indicators of quality ofenvironment and urban life with local collaborative networks and portraying the dimensions ofsustainability reveals a pedagogical path for the endogenous construction of possibilities ofunderstanding and evaluating key aspects of the production of urban spaces. We consider thepossibility of measuring social exclusion and social and environmental segregation from theimbalance between the dimensions of sustainability, translated into elements that combine aspectsin the environmental, social, economic, cultural and political dimension.